2015
DOI: 10.1186/1755-8794-8-s2-s7
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of disease-associated single nucleotide polymorphism influencing post-translational modification

Abstract: Post-translational modification (PTM) plays a crucial role in biological functions and corresponding disease developments. Discovering disease-associated non-synonymous SNPs (nsSNPs) altering PTM sites can help to estimate the various PTM candidates involved in diseases, therefore, an integrated analysis between SNPs, PTMs and diseases is necessary. However, only a few types of PTMs affected by nsSNPs have been studied without considering disease-association until now. In this study, we developed a new databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…Thus, we only consider two well-recognized features, protein interactions and conserved local sequence around phosphorylation sites. Since genetic variation changes phosphorylation sites or their interacting kinases [ 31 , 32 ], many methods have emerged to quantify the effects of SNVs (single nucleotide variants) on protein phosphorylation. ActiveDriver identified a specific p-site region in a given protein that has a significantly different mutation rate than expected, thereby finding cancer driver mutations [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we only consider two well-recognized features, protein interactions and conserved local sequence around phosphorylation sites. Since genetic variation changes phosphorylation sites or their interacting kinases [ 31 , 32 ], many methods have emerged to quantify the effects of SNVs (single nucleotide variants) on protein phosphorylation. ActiveDriver identified a specific p-site region in a given protein that has a significantly different mutation rate than expected, thereby finding cancer driver mutations [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that about 60% of Mendelian diseases are caused by amino acid substitutions [48]. A potential effect of SAVs on protein function is the disruption of PTMs [49]. For example, the potential for phosphorylation sites to be affected by amino acid variants is high, and there have been numerous examples of diseases associated naturally occurring variants that impact the phosphorylation status of proteins [50].…”
Section: Ptm-associated Mutation Collectionmentioning
confidence: 99%
“…It is reported that about 60% of Mendelian diseases are caused by amino acid substitutions [47]. A potential effect of SAVs on protein function is the disruption of PTMs [48]. For example, the potential for phosphorylation sites to be affected by amino acid variants is high and there have been numerous examples of diseases associated naturally occurring variants that impact the phosphorylation status of proteins [49].…”
Section: Ptm-associated Mutation Collectionmentioning
confidence: 99%